Development and Evaluation of a Brain-Based Learning Microsite for Geometric Transformation Learning - Muhtarom; Anindyo Windi Sulistyowarno; Ida Dwijayanti (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2026)
The limited availability of interactive learning media that align with students' cognitive processes and promote mathematical creative thinking remains a challenge in mathematics education. Therefore, this study aimed to develop a Brain-Based Learning microsite to enhance students' mathematical creative thinking. This study employed a Research and Development (R&D) method by integrating the ADDIE model with the Design Thinking approach. The developed learning media focused on the topic of geometric transformations for Grade 12 senior high school students. The participants consisted of 17 students in the experimental class and 31 students in the control class. Data were collected through expert validation sheets, mathematical creative thinking tests, and user response questionnaires. The data were analyzed using descriptive statistics, an independent-samples t-test, and N-gain analysis. The results indicated that the developed microsite was highly valid, obtaining validation scores of 88.75% from the media expert and 100% from the subject-matter expert. The user response questionnaire showed a practicality score of 90%, categorized as very good. The effectiveness analysis demonstrated a significant difference in mathematical creative thinking between the experimental and control classes, with students using the developed microsite achieving better performance. Furthermore, the experimental class obtained an N-gain score of 0.76, categorized as high, indicating substantial improvement in students' mathematical creative thinking. These findings suggest that the Brain-Based Learning microsite is a valid, practical, and effective learning medium for supporting mathematics learning and enhancing students' mathematical creative thinking.